A novel approach to biological risk surveillance in occupational hygiene: A case study on the use of quantitative microbial risk assessment to determine occupational risks for wastewater treatment plants workers in Costa Rica - Morales Mora, Eric (2023)
Wastewater treatment is essential for preventing infectious diseases and water pollution. To perform this process, workers operate and maintain wastewater treatment plants (WWTPs); thus, they are exposed to the many pathogens in domestic wastewater. Consequently, it is necessary assess occupational exposure to pathogens in WWTPs. Quantitative microbial risk assessment (QMRA) is an approach for estimating the risk posed by a specific pathogen which can be useful for occupational hygiene assessments of biological risk. In this study, we applied QMRA, informed by occupational field surveillance, to estimate the potential risk for WWTP workers. Furthermore, we used simulations to test additional control strategies such as personal protective equipment (PPE). The QMRA was conducted for three WWTPs in Costa Rica with data collected between May 2020 and May 2021. Observation in each workplace showed a need for more consistent application of risk reduction strategies in the work environment, especially in behavior, infrastructure, and use of appropriate PPE. Cryptosporidium sp., Giardia sp., norovirus, and enterovirus genus were measured and detected in the WWTPs, and the treatment performance was unsatisfactory. As a result, the total health disease burden was higher than the benchmark for drinking water recommended by WHO (1.00 × 10−6 DALY per person per year) by between one and three magnitudes orders in all WWTPs for the three exposure scenarios (operation, maintenance, and visitors). The simulation demonstrated that using PPE could reduce the estimated disease burden by nearly two orders of magnitude. Still, this control measure did not reach a level below the benchmark risk (less than 1.00 × 10−6 DALY per person per year) for the WWTP workers. This study highlights the importance of using PPE with other control measures, such as automation or barriers, to isolate exposure sources. However, this study employed an uncommon approach in occupational health and hygiene, which combined field inspections, survival analysis, and QMRA, using field surveillance to understand the occupational environment and potential exposure routes, which is crucial for hazard identification and risk assessment. In addition, exposure modeling and QMRA were used to simulate different control scenarios, providing a robust estimate of potential risks associated with occupational exposure.